Finding ‘Reasons to Stay’ Amidst Issues of Well-Being: A Case Study of Two Underserved Communities in Colombo - Iresha M. Lakshman; Mohideen M. Alikhan; Abdhullah Azam (European Scientific Journal, ESJ, 2020)
This paper attempts to explore the factors that attract and encourage individuals to live in low-income neighbourhoods in Colombo in spite of the many socioeconomic issues that are associated with such communities. Data was collected through 30 face-to-face in-depth interviews with residents from two underserved communities consisting of individuals with different migration experiences. The collected data was then analysed using the three-dimensional well-being model introduced by Pouw and McGregor (2014). The study revealed a situation of material and relational wellbeing intersecting to create a more practical kind of well-being in the communities studied. Of the two, material well-being had the strongest power to attract and retain residents in the neighbourhoods while relational wellbeing played a supportive role in terms of pulling people into the community. Subjective well-being, on the other hand, was identified as the strongest reason with a capacity to push people away from the community. However, this single push factor was not strong enough to overpower the pull effect of material and relational well-being, particularly because of the residents’ low-income status. The material benefits of living in the location facilitated by social ties offered by the neighbourhood kept these residents attracted and attached to these underserved communities.